Competencies for Health Communication Specialists: Survey of Health Communication Educators and Practitioners. Issue 6 (3rd June 2021) - Park, Sung-Yeon; Harrington, Nancy Grant; Crosswell, Laura H.; Parvanta, Claudia
ABSTRACT: For more than two decades, health communication educators and practitioners have been working toward establishing a competency model to guide health communication education. This article reports the results of a survey to identify competencies for health communication specialists with master's degrees. To prepare the survey, a working group drafted a competency list through reviewing the literature and soliciting feedback from attendees at a professional society meeting, resulting in lists of items reflecting 18 knowledge domains, 11 skill sets, and 14 application bundles labeled "abilities." The survey asked participants to rate the 43 items in terms of their importance and provide their opinions about the preparation of health communication specialists. The survey was disseminated online through professional associations and completed by 142 participants (74 educators and 68 practitioners). Nearly all of the 43 items were rated "somewhat important" or higher. The lists were reduced to 10 knowledge domains, three skill sets, and five abilities through factor analyses. Replication of the findings and triangulation with studies employing different research methods will help advance this line of inquiry.